The man who knew infinity [videorecording (DVD)] - Brown, Matthew, 1974-; Patel, Dev, 1990-; Irons, Jeremy, 1948-; Bhise, Devika; Kanigel, Robert (Paramount Home Entertainment, 2016)
Growing up poor in Madras, India, Srinivasa Ramanujan Iyengar earns admittance to Cambridge University during WWI, where he becomes a pioneer in mathematical theories with the guidance of his professor, G.H. Hardy.